Analysis of the Influence of Managerial Ownership, Audit Quality and Audit Committee on Income Management (Study on Manufacturing Companies in the Consumer Goods Sector Listed on the Indonesia Stock Exchange 2014-2018) - Sitanggang, Sri Ningsih; Ikhsan, Arfan; Nasirwan, Nasirwan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to examine the effect of managerial ownership, audit quality and audit committee on earnings management. The research was conducted at manufacturing companies in the consumer goods sector which were listed on the Indonesia Stock Exchange in 2014-2018. The sampling technique used purposive sampling technique and obtained 10 companies that became samples. Hypothesis testing is done by using multiple regression analysis. The results of this study indicate that: first, managerial ownership does not have a significant effect on earnings management. It can be seen that the t-count is smaller than the t-table (0.152 <1.678) with a significance value of 0.880> 0.05. Second, audit quality affects earnings management. It can be seen that the t-count is greater than the t-table (2.274> 1.678), with a significance value of 0.028 <0.05. Third, the audit committee has a significant effect on earnings management. It can be seen that the t-count is greater than the t-table (2.894 > 1.6 7 8), with a significance value of 0.006 <0.05. If reviewed together, the three variables of managerial ownership, audit quality, and audit committee have an effect of 25.4% on earnings management.